Adaptasi perubahan spektrum SMK 2016 oleh guru SMK Program Keahlian Teknik Konstruksi dan Properti - Ahmad Rifqi Asrib; Anas Arfandi (Universitas Negeri Makassar, 2020)
This activity aims to increase the understanding of teachers of the Department of Building Engineering at SMK 4 Gowa about irrigation and its buildings. The method used in this community partnership program, the mentoring method and the participatory rural approach (PRA) method. Mentoring method are used to improve teachers' understanding of irrigation networks and irrigation structures. The PRA method is carried out to arouse the partner's sense of belonging to the product to be developed, and the partner's sense of responsibility towards the product and the environment around it. The initial survey was conducted to see the extent of respondents' initial understanding prior to the implementation of PKM on the understanding and ability of teachers to understand the material to be provided. After the PKM implementation activities, the survey was again conducted to measure the level of understanding of respondents after the implementation of the PKM activities and to be a measure of the effectiveness of the implementation of the PKM to vocational teachers in the construction and property engineering expertise program. The results of the activity show that most teachers have only understood the irrigation material in the Fair category. There is even an average of 12 percent of teachers whose understanding is still lacking. The teachers also have not been able to distinguish irrigation buildings very well. After the implementation of the PKM activity, the teachers participating in the activity experienced a very significant increase in understanding. Teachers' understanding of the category was very good at 4.36% to 41.28%. Good category from 20.00% to 55.64% even after the activity, all teachers had understood the material about irrigation and its buildings.